Public Perception of Polygamy in Makassar, Indonesia: Cultural Perspective and Islamic Law - Ridwan, Muhammad Saleh; Abdullah, Wahidah; Idham, Idham (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
One of the issues in Islamic law that is often debated is the case of polygamy that occurs in society in Indonesia. The perception of people in Makassar City, South Sulawesi about polygamy is still very taboo. This assumption arises because of their erroneous understanding of polygamy. This article aimed to discuss the underlying factors of polygamous marriages in Makassar. The research used empirical methods with survey techniques, analyzed with Islamic law theory. The current research was designed as a survey which involved 80 participants, who consisted of 30 polygamous actors and 50 people from monogamous relationships. Instruments used in this study were a close-ended questionnaire and an open interview guideline with polygamists. The results showed that among the Makassarian community members who agreed with the practice of polygamy, there was a group of people who considered polygamy as a disgrace to the family or an act of demeaning women. It was reported that many polygamous actors conducted polygamy without any consent from their first wives. The survey also uncovered several factors that provoked polygamy practices in Makassar. These factors include female infertility, men’s sexual needs, the Prophet’s Sunnah, incurable diseases, and ignorance. Moreover, the majority of polygamous actors in Makassar chose not to register their second marriage at the Civil Registry office due to the state's convoluted bureaucracy and the law that prohibits government employees from being polygamous.